Answer:
![\left \{ {{u'=v} \atop {v'=5v-6u-5\sin(2t)}} \right. \\u(0)=-5;u'(0)=2](https://img.qammunity.org/2021/formulas/mathematics/college/nm5fzv2j5ypn4y26h8ufaymxyoz5s8mq1j.png)
Explanation:
The given initial value problem is;
![y''-5y'+6y=-5\sin(2t)---(1)\\y(0)=-5,y'(0)=2](https://img.qammunity.org/2021/formulas/mathematics/college/k0q5sjuwkzle7p0pyr82fv0fgpbdas8r7t.png)
Let
![u(t)=y(t)----(2)\\v(t)=y'(t)----(3)](https://img.qammunity.org/2021/formulas/mathematics/college/rlxresbs8ekcc9220836keb7hch811timx.png)
Differentiating both sides of equation (1) with respect to
, we obtain:
![u'(t)=y'(t)---(4)\\ \\\implies u'(t)=v(t)---(5)](https://img.qammunity.org/2021/formulas/mathematics/college/1e1jgcelm69mid0t1u8zt9r8f6s6q669wr.png)
Differentiating both sides of equation (2) with respect to
gives:
![v'(t)=y''(t)----(6)](https://img.qammunity.org/2021/formulas/mathematics/college/p477puxynogwyb9h91709p409topezlj95.png)
From equation (1),
![y''=5y'-6y-5\sin(2t)\\y''=5v(t)-6u(t)-5\sin(2t)\\\implies v'(t)=5v(t)-6u(t)-5\sin(2t)----(7)](https://img.qammunity.org/2021/formulas/mathematics/college/2a0o3ycoz4p2006clm91j6dcip58zh48sm.png)
Putting t=0 into equation (2) yields
![u(0)=y(0)\\\implies u(0)=-5](https://img.qammunity.org/2021/formulas/mathematics/college/8hyxkm3jae9se3pamlk6l91hqt7dxaiv8v.png)
Also putting t=0 into equation (3)
![u'(0)=y'(0)\\u'(0)=2](https://img.qammunity.org/2021/formulas/mathematics/college/9xyza4a0njngdoxuijf10ci62lyjep4gdv.png)
The system of first order equations is:
![\left \{ {{u'=v} \atop {v'=5v-6u-5\sin(2t)}} \right. \\u(0)=-5;u'(0)=2](https://img.qammunity.org/2021/formulas/mathematics/college/nm5fzv2j5ypn4y26h8ufaymxyoz5s8mq1j.png)